Broncho-Obstructive Syndrome in Young Children: Clinic, Diagnosis and Treatment - Sh.M. Ibatova; D.Kh. Mamatkulova (Euro Asian Journal Publishing, 2024)
Most diseases of the bronchopulmonary system occur with broncho-obstructive syndrome (BOS), among which we should note congenital and hereditary pathology of the respiratory system, bronchial malformations, respiratory distress syndrome, primary immunodeficiency conditions, aspiration of foreign bodies, perinatal pathology, gastroesophageal reflux, enlarged intrathoracic lymph nodes, hyperplasia thymus, tumors, etc. Clinical manifestations of biofeedback consist of prolongation of exhalation and the appearance of expiratory noise. The diagnosis is made on the basis of clinical and anamnestic data, the results of a physical and functional examination. Treatment of biofeedback should be aimed at eliminating the cause of the disease that led to the development of obstruction
Keywords: Broncho-obstructive syndrome; children; clinic